THE EFFECT OF NOMINAL INVESTMENT CAPITAL, RETURN, RISK PERCEPTION, HEALTH, AND KNOWLEDGE ON STUDENT INTEREST WITH INCOME AS AN INVESTMENT MODERATION VARIABLES IN INVESTMENT GALLERY INDONESIA STOCK EXCHANGE UNIVERSITAS SUMATERA UTARA - Nasution, Muhammad Pintor (International Journal of Public Budgeting, Accounting and Finance, 2019)
The objective of the research was to analyze and find out the influence of nominal investment capital, return, risk perception, health, and knowledge on the interest in investment simultaneously and partially at Galery Investasi BEI-USU and to examine whether earnings could moderate the correlation of nominal investment capital, return, risk perception, health, and knowledge with the interest in investment at Galery Investasi BEI- USU. The population was 81 students who opened their stock accounts in Galery Investasi BEI-USU, and all of them were used as the samples, (census sampling technique). The data were analyzed by using multiple linear regression analysis and residual test for moderating variable. The result of the research showed that, simultaneously, the variables of nominal investment capital, return, risk perception, health, and knowledge had significant influence of the interest in investment at Galery Investasi BEI-USU. Partially, return and risk perception had positive and significant influence on the interest in investment, nominal investment capital had negative but significant on the interest in investment, while health and knowledge did not have any influence on the interest in investment. Earnings could moderate the correlation of nominal investment capital, return, risk perception, health, and knowledge with the interest in investment.